Klio hat jetzt Internet Historische Narrative auf Youtube - Darstellung, Inszenierung, Aushandlung - Baur, Kilian; Trautmannsberger, Robert (Medien der Geschichte, 2023)
History videos on YouTube have obtained an enormous reach and relevance in the transmission of historical and political content. This edited volume examines media stagings, specific features in the historical portrayals of certain epochs, and processes of negotiating historical culture on YouTube. It makes a contribution to defining the relationship between history and popular media, and the challenges that this entails.